Smooth and Topological Equivalence of Functions on Surfaces - Sharko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We obtain conditions under which the Morse functions defined on surfaces are smooth equivalent and functions with isolated critical (singular) points are topologically equivalent.